Proteomics fingerprinting reveals importance of iron and oxidative stress in Streptomyces scabies–Solanum tuberosum interactions - Giroux, Lauriane; Isayenka, Iauhenia; Lerat, Sylvain; Beaudoin, Nathalie; Beaulieu, Carole (Frontiers in Microbiology, 2024)
The Gram-positive actinobacterium Streptomyces scabies is the major causal agent of potato common scab. The main pathogenicity factor is thaxtomin A, a phytotoxin that causes atypical cell death, although other secondary metabolites have been described to play a role in S. scabies virulence. Despite this, many aspects of the interaction between S. scabies and its primary host Solanum tuberosum L. remain to be elucidated. This study revealed changes in the bacterial proteome in the presence of in vitro produced tubers of the Russet Burbank and Yukon Gold potato cultivars. Potato microtubers caused an increase in the amount of bacterial proteins involved in stress and defense, secondary metabolism and cell differentiation, as well as secreted proteins. Cocultivation of S. scabies with potato microtubers induced abundance of proteins implicated in the siderophore pyochelin biosynthesis, which was consistent with a significant decrease in the iron content in the culture medium. Proteins involved in oxidative stress perception and response were also upregulated in the presence of the host, suggesting that S. scabies was defending against ROS produced by potato tubers.